Porphyromonas gingivalis Induces Increases in Branched-Chain Amino Acid Levels and Exacerbates Liver Injury Through livh/livk - Wu, Leng; Shi, Rui; Bai, Huimin; Wang, Xingtong; Wei, Jian; Liu, Chengcheng; Wu, Yafei (Frontiers in Cellular and Infection Microbiology, 2022)
Porphyromonas gingivalis, a keystone periodontal pathogen, has emerged as a risk factor for systemic chronic diseases, including non-alcoholic fatty liver disease (NAFLD). To clarify the mechanism by which this pathogen induces such diseases, we simultaneously analyzed the transcriptome of intracellular P. gingivalis and infected host cells via dual RNA sequencing. Pathway analysis was also performed to determine the differentially expressed genes in the infected cells. Further, the infection-induced notable expression of P. gingivalis livk and livh genes, which participate in branched-chain amino acid (BCAA) transfer, was also analyzed. Furthermore, given that the results of recent studies have associated NAFLD progression with elevated serum BCAA levels, which reportedly, are upregulated by P. gingivalis, we hypothesized that this pathogen may induce increases in serum BCAA levels and exacerbate liver injury via livh/livk. To verify this hypothesis, we constructed P. gingivalis livh/livk-deficient strains (∆livk, ∆livh) and established a high-fat diet (HFD)-fed murine model infected with P. gingivalis. Thereafter, the kinetic growth and exopolysaccharide (EPS) production rates as well as the invasion efficiency and in vivo colonization of the mutant strains were compared with those of the parental strain. The serum BCAA and fasting glucose levels of the mice infected with either the wild-type or mutant strains, as well as their liver function were also further investigated. It was observed that P. gingivalis infection enhanced serum BCAA levels and aggravated liver injury in the HFD-fed mice. Additionally, livh deletion had no effect on bacterial growth, EPS production, invasion efficiency, and in vivo colonization, whereas the ∆livk strain showed a slight decrease in invasion efficiency and in vivo colonization. More importantly, however, both the ∆livk and ∆livh strains showed impaired ability to upregulate serum BCAA levels or exacerbate liver injury in HFD-fed mice. Overall, these results suggested that P. gingivalis possibly aggravates NAFLD progression in HFD-fed mice by increasing serum BCAA levels, and this effect showed dependency on the bacterial BCAA transport system.